Diffusion-Weighted Magnetic Resonance Imaging in the Diagnosis and Staging of Bladder Cancer - I. G. Frolova; E. G. Grigor'ev; S. A. Velichko; A. V. Usova; N. G. Trukhacheva (Вестник рентгенологии и радиологии, 2020)
This scientific review assesses the current diagnostic capabilities of diffusion-weighted images used in the magnetic resonance imaging protocol for bladder cancer. It actualizes this impulse sequence employed within the framework of a multiparametric MRI study as one of the functional techniques. The review deals with the possibilities of diffusion-weighted images used in an independent version and in combination with T2-weighted images to visualize a tumor, postoperative changes, and associated pathology. It gives differential diagnostic criteria in identifying the extent of tumor invasion, including that with accuracy assessment according to the measured diffusion coefficient.The sources of the review are publications included in the peer-reviewed databases PubMed, Scopus, eLIBRARY and the open sources Google Scholar, Researchgate.